#MeToo at the U.S.-Mexico Border: Travelers’ Experiences of Gender-Based Misconduct - Updegrove, Alexander H. (American journal of criminal justice, 2022)
This exploratory study used semi-structured interviews with 90 U.S.-Mexico port-of-entry-crossers to investigate whether they or someone they know experienced gender-based misconduct while crossing. Results revealed U.S. Customs officers (1) asked for or gave travelers a phone number; and (2) made inappropriate comments or queries, such as suggestive comments and asking travelers' about their relationship status. Other experiences mentioned included unwanted touching and officers misusing private information obtained from travelers' legal documents to contact them on social media. Participants also described how fear of retaliation rendered them suitable targets for these behaviors. Finally, participants referenced capable guardianship by noting how the presence of family members influenced Customs officers' behavior.